2019
DOI: 10.3389/fimmu.2019.01923
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A Can Promote Propionibacterium acnes-Induced Sarcoidosis-Like Granulomatosis in Mice

Abstract: The etiology of sarcoidosis is unknown. In this study, Propionibacterium acnes (PA) was used to induce sarcoidosis-like granulomatous inflammation in a mouse model. Wild-Type (WT) C57BL/6 mice were divided into three groups: (1) WT-PA group; (2) WT-PA + Incomplete Freund's Adjuvant (IFA) group; and (3) WT-PBS group. Loose granuloma formation was observed in the lungs on day 56 in the WT-PA and WT-PA + IFA groups. The proportions of peripheral Th17 cells in the WT-PA ( p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…So far, no specific C. acnes phylotype has been associated with sarcoidosis. The involvement of C. acnes in sarcoidosis is also supported by experiments in mice (Werner et al, 2017;Song et al, 2019). As a possible disease scenario, invasive C. acnes, possibly derived from the skin, could result in a latent, intracellular state, for example in macrophages.…”
Section: Sarcoidosismentioning
confidence: 80%
“…So far, no specific C. acnes phylotype has been associated with sarcoidosis. The involvement of C. acnes in sarcoidosis is also supported by experiments in mice (Werner et al, 2017;Song et al, 2019). As a possible disease scenario, invasive C. acnes, possibly derived from the skin, could result in a latent, intracellular state, for example in macrophages.…”
Section: Sarcoidosismentioning
confidence: 80%
“…First, SAA was found to contribute to Th17-cell proliferation and Th17 cytokine production [ 8 ]. Th17-cells have been found to contribute in sarcoidosis pathogenesis [ 9 , 10 ] and in granuloma formation [ 11 , 12 ]. Second, Chen et al [ 13 ] studied the role of SAA in the regulation of granulomatous inflammation in sarcoidosis and found significant presence of SAA in granulomas of sarcoidosis patients which exceeded the intensity of SAA staining found in tissue from patients with tuberculosis, granulomatous polyangiitis, or hypersensitivity pneumonitis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of IL-35 in granulomatous inflammation was further analyzed using a mouse model of sarcoidosis granuloma which was previously established by our study group (20). The findings suggested that IL-35 and IL-21 levels in the BALF of mouse models of sarcoidosis granuloma were elevated, and the proportions of Bregs and Tfh cells in the peripheral blood and BALF also increased, however the proportion of Tregs decreased.…”
Section: Discussionmentioning
confidence: 70%